Mangrove Ecology, Silviculture and Conservation - Saenger, Peter; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2002)
Mangroves are a fascinating group of plants that occur on tropical and subtropical shorelines of all continents, where they are exposed to saltwater inundation, low oxygen levels around their roots, high light and temperature conditions, and periodic tropical storms. Despite these harsh conditions, mangroves may form luxuriant forests which are of significant economic and environmental value throughout the world - they provide coastal protection and underpin fisheries and forestry operations, as well as a range of other human activities. This book provides an up-to-date account of mangrove plants from around the world, together with silvicultural and restoration techniques, and the management requirements of these communities to ensure their sustainability and conservation. All aspects of mangroves and their conservation are critically re-examined. Those activities which threaten their ongoing survival are identified and suggestions are offered to minimise their effects on these significant plant communities.
1. Introduction: The Mangrove Environment -- 2. The Mangrove Flora -- 3. Adapting to the Mangrove Environment -- 4. Physico-chemical Factors and Mangrove Performance -- 5. Biotic Interactions and Mangrove Performance -- 6. Mangrove Structure and Classification -- 7. The Value of Mangroves -- 8. Mangrove Silviculture and Restoration -- 9. Conservation and Management of Mangroves -- 10. References.
Keywords: Plant ecology; Ecology .; Forestry; Botany; Plant Ecology; Ecology; Forestry; Plant Science